2021
DOI: 10.1177/14791641211058855
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of FOS-like antigen 1 represses restenosis via the ERK/AP-1 pathway in type 2 diabetic mice

Abstract: Restenosis is a major limiting factor for a successful outcome in type 2 diabetes (T2D) patients undergoing percutaneous coronary intervention (PCI). The aim of this study is to explore the role and regulatory mechanism of FOS-like antigen 1 (FOSL1) in restenosis in T2D. A T2D with restenosis mouse model was established by the combination of high-fat diet and streptozotocin injection and by wire-injury. High glucose (HG)-treated vascular smooth muscle cells (VSMCs) were used to mimic T2D in vitro. The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Research has shown that LMNA (lamin A/C) [314], VCAM1 [281], MAPK6 [403], DDX3X [366], SHMT2 [459], PHGDH (phosphoglycerate dehydrogenase) [560], S100A9 [433], SNCA (synuclein alpha) [335], TP63 [313], FOSL2 [1449], FHL2 [321], ATF3 [55], FOSL1 [379], DYSF (dysferlin) [475], CA4 [547], S100A8 [58] and MPO (myeloperoxidase) [521] plays an important role in the pathogenesis of lung cancer. LMNA (lamin A/C) [676], VCAM1 [657], DDX3X [708], S100A9 [745], FKBP5 [747], SNCA (synuclein alpha) [690], FOSL2 [1450], FHL2 [680], ATF3 [63], FOSL1 [718], S100A8 [67] and MPO (myeloperoxidase) [787] altered expression is associated with poor prognosis of diabetes mellitus. LMNA (lamin A/C) [676], VCAM1 [986], PHGDH (phosphoglycerate dehydrogenase) [1100], S100A9 [1045], FKBP5 [1046], FHL2 [1003], ATF3 [85] and MPO (myeloperoxidase) [1084] plays an important role in the development of obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that LMNA (lamin A/C) [314], VCAM1 [281], MAPK6 [403], DDX3X [366], SHMT2 [459], PHGDH (phosphoglycerate dehydrogenase) [560], S100A9 [433], SNCA (synuclein alpha) [335], TP63 [313], FOSL2 [1449], FHL2 [321], ATF3 [55], FOSL1 [379], DYSF (dysferlin) [475], CA4 [547], S100A8 [58] and MPO (myeloperoxidase) [521] plays an important role in the pathogenesis of lung cancer. LMNA (lamin A/C) [676], VCAM1 [657], DDX3X [708], S100A9 [745], FKBP5 [747], SNCA (synuclein alpha) [690], FOSL2 [1450], FHL2 [680], ATF3 [63], FOSL1 [718], S100A8 [67] and MPO (myeloperoxidase) [787] altered expression is associated with poor prognosis of diabetes mellitus. LMNA (lamin A/C) [676], VCAM1 [986], PHGDH (phosphoglycerate dehydrogenase) [1100], S100A9 [1045], FKBP5 [1046], FHL2 [1003], ATF3 [85] and MPO (myeloperoxidase) [1084] plays an important role in the development of obesity.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to involve in the Wnt signaling pathway, FOSL1 can inhibit adipocyte differentiation by inhibiting C/EBPa (46). FOSL1 is a potential therapeutic target to prevent diabetes-induced atherosclerosis (47). The existing literatures showed that lncRNAs, such as TCONS_00006525, TCONS_00046551, and TCONS_00000528 in the regulatory network are involved in the WNT signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is evidence that targeted interventions for diabetic foot ulcers and multidisciplinary care can reduce the loss of limbs, the progress has been slow so far [22][23][24]. Although the elderly population with glycosuria amputation is declining, the number of patients with type 2 diabetes has increased in some countries [25,26]. In this experiment, the diabetic mouse foot ulcer model was established to observe the curative effect of external ulcer powder on mouse foot ulcers and the expression of angiogenesis-related factors ERK and VEGF.…”
Section: Discussionmentioning
confidence: 99%